Ginsenoside Re protects against phencyclidine-induced behavioral changes and mitochondrial dysfunction via interactive modulation of glutathione peroxidase-1 and NADPH oxidase in the dorsolateral cortex of mice. (December 2017) - Tran, The-Vinh; Shin, Eun-Joo; Dang, Duy-Khanh; Ko, Sung Kwon; Jeong, Ji Hoon; Nah, Seung-Yeol; Jang, Choon-Gon; Lee, Yu Jeung; Toriumi, Kazuya; Nabeshima, Toshitaka; Kim, Hyoung-Chun
Abstract: We investigated whether ginsenoside Re (Re) modulates phencyclidine (PCP)-induced sociability deficits and recognition memory impairments to extend our recent finding. We examined the role of GPx-1 gene in the pharmacological activity of Re against mitochondrial dysfunction induced by PCP in the dorsolateral cortex of mice. Since mitochondrial oxidative stress activates NADPH oxidase (PHOX), we applied PHOX inhibitor apocynin for evaluating interactive modulation between GPx-1 and PHOX against PCP neurotoxicity. Sociability deficits and recognition memory impairments induced by PCP were more pronounced in GPx-1 knockout (KO) than in wild type (WT) mice. PCP-induced mitochondrial oxidative stress, mitochondrial dysfunction, and membrane translocation of p47 phox were more evident in GPx-1 KO than in WT. Re treatment significantly attenuated PCP-induced neurotoxic changes. Re also significantly attenuated PCP-induced sociability deficits and recognition memory impairments. The attenuation by Re was comparable to that by apocynin. The attenuation was more obvious in GPx-1 KO than in WT. Importantly, apocynin did not show any additional positive effects on the neuroprotective activity of Re, indicating that PHOX is a molecular target for therapeutic activity of Re. Our results suggest that Re requires interactive modulation between GPx activity and PHOX (p47 phox ) to exhibit neuroprotective potentials against PCP insult. Graphical abstract: Highlights: Genetic depletion of GPx-1 facilitates PCP-induced mitochondrial dysfunction, oxidative parameters and PHOX activity. Genetic depletion of GPx-1 facilitates sociability deficits and recognition memory impairments induced by PCP. Re-mediated protective potentials against PCP required the interactive modulation between GPx-1 and PHOX (p47 phox ).